Evaluación de la pérdida de rendimiento causado por el carbón del maní - Paredes, Juan Andrés; Gonzalez, Noelia; Miretti, Esteban; Suarez, Lautaro; Bricchi, L.; Rago, Alejandro Mario (Centro de Ingenieros Agrónomos General Cabrera, 2024)
Ponencia y poster